Effect of composition on electrical properties of lead-free Bi0.5(Na0.80K0.20)0.5TiO3-(Ba0.98Nd0.02)TiO3piezoelectric ceramics - Pharatree Jaita (2018)
Lead-free piezoelectric ceramics with the composition of (1-x)Bi 0.5 (Na 0.80 K 0.20 ) 0.5 TiO 3 -x(Ba 0.98 Nd 0.02 )TiO 3 or (1-x) BNKT-xBNdT (with x = 0-0.20 mol fraction) have been synthesized by a conventional mixed-oxide method. The compositional dependence of phase structure and electrical properties of the ceramics were systemically studied. The optimum sintering temperature of all BNKT-BNdT ceramics was found to be 1125°C. X-ray diffraction pattern suggested that BNdT effectively diffused into BNKT lattice during sintering to form a solid solution with a perovskite structure. Scanning electron micrographs showed a slight reduction of grain size when BNdT was added. It was found that BNKT-0.10BNdT ceramic exhibited optimum electrical properties (ε r = 1716, tanδ = 0.0701, T c = 327°C, and d 33 = 211 pC/N), suggesting that this composition has a potential to be one of a promising lead-free piezoelectric candidate for dielectric and piezoelectric applications. © 2013 AIP Publishing LLC.